“I am the gatekeeper”: why and how ministerial media advisers have been empowered - Johansson, Karl Magnus (Frontiers in Political Science, 2024)
Although policy advisers have been amply studied, far fewer studies have examined media advisers. And, so far, adviser research has offered few insights into the relationship between these two key groups of political staffers. This article claims that media advisers have been empowered. It offers a rational functionalist explanation, which emphasises concerns about functional efficiency. Media generates functional pressures for the institutional strengthening of media advisers, solidifying their role. This argument is examined empirically through a case study of ministerial media adviser (MMA) empowerment in Sweden, based on interviews conducted among MMAs and political journalists. The data tell us that MMAs are on the rise, that they have become more controlling toward journalists and more assertive within ministerial staff. In the process, MMAs have come to constitute a category of their own as they have converged among themselves but diverged from policy advisers. The interview evidence indicates that MMAs also have a role in government policy, as the media has contributed to more integration of communication and policy, but additional research is needed. Overall, this work has implications for research on political communication, executives, and advisers—especially for debates about political professionals in government.